MicroRNAs in the pathogenesis of renal cell carcinoma and their diagnostic and prognostic utility as cancer biomarkers - Fedorko, Michal; Pacik, Dalibor; Wasserbauer, Roman; Juracek, Jaroslav; Varga, Gabriel; Ghazal, Motasem; Nussir, Mohamed I (The International journal of biological markers, 2016)
PURPOSE: To provide information about the role of microRNAs in the pathogenesis of renal cell carcinoma (RCC) and their diagnostic and prognostic utility as cancer biomarkers. METHODS: A literature search was performed in the PubMed and Web of Science databases using the keywords "renal cancer/renal cell carcinoma/kidney cancer" and "miR*/miRNA*/microRNA*". Articles dealing with the role of miRNAs in the pathogenesis of RCC, diagnostic miRNAs and prognostic miRNAs were separated. RESULTS: MiRNAs act both as oncogenes and tumor suppressors. They regulate apoptosis, cell growth, migration, invasion, proliferation, colony formation and angiogenesis through target proteins involved in several signaling pathways, and they are involved in key pathogenetic mechanisms such as hypoxia (HIF/VHL dependent) and epithelial-to-mesenchymal transition. Differentially expressed miRNAs can discriminate either tumor tissue from healthy renal tissue or different RCC subtypes. Circulating miRNAs are promissing as diagnostic biomarkers of RCC. Information about urinary miRNAs associated with RCC is sparse. Detection of a relapse is another implication of diagnostic miRNAs. The expression profiles of several miRNAs correlate with the prognosis of RCC patients. Comparison between primary tumor tissue and metastasis may help identify high-risk primary tumors. Finally, response to target therapy can be estimated thanks to differences in miRNA expression in tissue and serum of therapy-resistant versus therapy-sensitive patients. CONCLUSIONS: Our understanding of the role of microRNAs in RCC pathogenesis has been increasing dramatically. Identification and validation of their gene targets may have direct impact on developing microRNA-based anticancer therapy. Several microRNAs can serve as diagnostic and prognostic biomarkers.
Keywords: Biomarkers, Tumor; nádorové buněčné linie; karcinom z renálních buněk; nádorové biomarkery; PubMed; mikro RNA; Carcinoma, Renal Cell; Prognosis; Cell Line, Tumor; regulace genové exprese u nádorů; Humans; Gene Expression Regulation, Neoplastic; lidé; proliferace buněk; Cell Proliferation; prognóza; MicroRNAs